CRISPR-Cas9 knockdown of ESR1 in preoptic GABA-kisspeptin neurons suppresses the preovulatory surge and estrous cycles in female mice - Jenny Clarkson; Siew Hoong Yip; Robert Porteous; Alexia Kauff; Alison K Heather; Allan E Herbison (eLife, 2023)
Evidence suggests that estradiol-sensing preoptic area GABA neurons are involved in the preovulatory surge mechanism necessary for ovulation. In vivo CRISPR-Cas9 editing was used to achieve a 60–70% knockdown in estrogen receptor alpha (ESR1) expression by GABA neurons located within the regions of the rostral periventricular area of the third ventricle (RP3V) and medial preoptic nuclei (MPN) in adult female mice. Mice exhibited variable reproductive phenotypes with the only significant finding being mice with bilateral ESR1 deletion in RP3V GABA neurons having reduced cFos expression in gonadotropin-releasing hormone (GnRH) neurons at the time of the surge. One sub-population of RP3V GABA neurons expresses kisspeptin. Re-grouping ESR1-edited mice on the basis of their RP3V kisspeptin expression revealed a highly consistent phenotype; mice with a near-complete loss of kisspeptin immunoreactivity displayed constant estrus and failed to exhibit surge activation but retained pulsatile luteinizing hormone (LH) secretion. These observations demonstrate that ESR1-expressing GABA-kisspeptin neurons in the RP3V are essential for the murine preovulatory LH surge mechanism.